Modeling the Steering of International Roaming Traffic - Martins, Carlos Lúcio (2017)
Telecommunications operators offering international roaming services need to decide to which foreign networks they should steer their customers towards, in order to benefit from the best wholesale commercial conditions. This operational managerial decision translates into a least-cost traffic routing problem for which five mixed integer linear programming models, corresponding to the most used commercial agreements in the industry, are hereby introduced. The models are based on a minimum cost flow problem over a layered network following an underlying year-planning managerial approach, with multi-period decision dependency and in the presence of uncertainty. A computational experiment is carried out using a comprehensive framework designed to generate structured semi-random instances that simulate realistic market and business scenarios. Results for this experiment are discussed according to business sustainability performance metrics and confirm the soundness of the models. Given the nature of the problem we consider that the computational effort required is low.